TINJAUAN KELENGKAPAN PENGISIAN CATATAN PERKEMBANGAN PASIEN TERINTEGRASI ( CPPT ) DALAM MENINGKATKAN KOMUNIKASI EFEKTIF ANTAR TENAGA KESEHATAN DI RUANG RAWAT OBGYN RUMAH SAKIT UMUM UNIVER - Meliana; Kanjeng Gamas Brajamusti (MEDICORDHIF Jurnal Rekam Medis, 2023)
The integrated patient progress record (CPPT) form contains information about the patient's identity, important notes, authentication, and good notes in the form of writings on the health services that have been provided to the patient. To coordinate or collaborate between health workers in documenting health services for patients in all polys / clinics in the Hospital, one of which is the Obgyn Room. This study aims to get an overview of the Completeness of Filling in the Integrity Patient Development Record (CPPT) in the Obgyn Inpatient Room of UKI Hospital. The study starts in June – August 2022. The research design used, namely the descriptive method, is to describe the research by conducting interviews and observations with Qualitative and Quantitative approaches. In this scientific paper study, researchers sampled 77 CPPT forms. The results of the study obtained 77 samples studied, obtained complete as many as 27 (35%) CPPT forms and incomplete ones as many as 50 (69.9%) CPPT forms. It can be concluded that UKI General Hospital already has Standard Operating Procedures for filling cppt. We recommend that the doctor again check the instructions that have been given to find out if it has gone right Keywords : Effective Communication, Completeness, Integrated Patient Development Record.